The impact of the Corona pandemic on the Saudi banking sector, a study applied to Saudi banks - Al- Qahtani, Munira Saeed (Journal of Economic, Administrative and Legal Sciences, 2022)
The global health crisis resulting from spread of new Corona epidemic, with regard to the banking sector across the world, showed that the mandatory quarantine period imposed by most countries around the world constituted an increasing pressure of risks on banking activity, especially banks active in loans to companies after many forced Institutions around the world to stop productive or industrial activity, and thus the crisis revealed that bank loans during this health crisis were not equal between one sector and another. From this standpoint came the idea of ​​the research, and the researcher relied on the descriptive approach in its theoretical side in order to gain familiarity with the various aspects of the study, and the analytical method for the financial statements of Saudi banks during the nine months and the fourth quarter of 2020 compared to now during the nine months and the fourth quarter of 2019.The study concluded some results and recommendations, including: Increasing demand for loans granted by banks to the corporate sector, in order to control the repercussions of the Corona pandemic, and also the profits of most of the Saudi banks that compose the study sample decreased, except for (Al- Ahly Commercial, Al- Rajhi Bank and Saudi Investment Bank) and their net income from The different operations are clearly in the nine months of the year 2020 compared to the nine months of last year, and the provision for credit losses for most banks in the study sample also increased due to the repercussions of the Corona pandemic on the global economy in general in 2020, on the Saudi economy as a whole, and on the Saudi banking sector In particular. Work must also be made to develop legislation, legal and regulatory frameworks from the Saudi Arabian Monetary Agency, which work to ensure that banks benefit from the rescue packages and support measures taken by the institution to support the Saudi banking sector, and work to take into account the proposals of the Basel Committee in terms of overcoming the negative effects of banking risks, Especially in this crisis and the rapid spread of the virus, in an effort to maintain financial stability.
Keywords: Corona pandemic (Covid-19); banks; profits of Saudi banks